(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2023)
A bioactive substance derived from Chinese herbal remedies with known biological activity and pharmacological effects is known as a traditional Chinese medicine (TCM) monomer. It has drawn a lot of interest for the treatment of neurological disorders. However, TCM monomers’ weak solubility and poor blood-brain barrier (BBB) crossing capabilities restrict their use. With special benefits including low toxicity, low immunogenicity, high blood stability, and the capacity to pass the blood-brain barrier, exosomes—small extracellular vesicles (EVs)) with a diameter of 30 to 150 nm—can be used as drug delivery vehicles that directly target cells or tissues. In addition to comparing exosomes with other comparable drug delivery methods, this study covers the biogenesis, components, stability, surface modification, separation technique, benefits, and drawbacks of exosomes as drug carriers. Exosome-encapsulated TCM monomers also have neuroprotective effects, such as anti-oxidation, anti-apoptosis, anti-inflammation, and anti-mitophagy, in a variety of neuronal diseases, such as multiple sclerosis, Alzheimer’s disease, Parkinson’s disease, and cerebral ischemia and reperfusion (CI/R) injury. They also have anti-drug resistance, anti-tumorigenesis, and anti-angiogenesis properties, as well as promoting the development of an exosome-based delivery tool in targeted therapy for neuronal diseases.